Organic iron (III) complexing ligands during an iron enrichment experiment in the western subarctic North Pacific - Yoshiko Kondo; Shigenobu Takeda; Jun Nishioka; Hajime Obata; Ken Furuya; William Keith Johnson; C. S. Wong (Geophysical Research Letters)
Complexation of iron (III) with natural organic ligands was investigated during a mesoscale iron enrichment experiment in the western subarctic North Pacific (SEEDS II). After the iron infusions, ligand concentrations increased rapidly with subsequent decreases. While the increases of ligands might have been partly influenced by amorphous iron colloids formation (12–29%), most in‐situ increases were attributable to the <200 kDa fraction. Dilution of the fertilized patch may have contributed to the rapid decreases of the ligands. During the bloom decline, ligand concentration increased again, and the high concentrations persisted for 10 days. The conditional stability constant was not different between inside and outside of the fertilized patch. These results suggest that the chemical speciation of the released iron was strongly affected by formation of the ligands; the production of ligands observed during the bloom decline will strongly impact the iron cycle and bioavailability in the surface water.